Application of Surface Molecular Imprinting Technology in Sample Pretreatment for Food Analysis: A Review - SHI Xinyu, WANG Qing, ZHANG Yanqing (Shipin Kexue, 2024)
In recent years, surface molecular imprinting technology has drawn a lot of attention for its application in sample pretreatment for food analysis. Due to the complexity of the food matrix, there are high requirements for the sensitivity and selectivity of food detection. Surface molecularly imprinted polymers are polymerized on the surface of a solid support, and when the template is removed, a cavity is formed to adsorb the target or its structural analogues. Various targets ranging from contaminants, toxicants and adulterants to natural active ingredients can be efficiently imprinted, thus making it easier to extract them from food matrices like dairy products, fruits and vegetables, meat products, and drinks. Owing to their potential to improve the selectivity and adsorption capacity and hence the accuracy of analysis, multi-template imprinting strategies and virtual template imprinting have become research hotspots. This article summarizes the design strategies, carrier types, preparation methods of surface molecularly imprinted polymers and reviews the progress made over the past five years in their application in sample pretreatment for food analysis in order to provide a reference for the application of surface molecularly imprinted technology in food analysis.